The incompatibility of antenatal care referrals in Reda Bolo Hospital - Anriani, Selvy; Rumopa, Harold I.M. (Institute of Computer Science (IOCS), 2024)
In the era of Indonesia's National Health Insurance or Jaminan Kesehatan Nasional (JKN), antenatal care services (ANC), have become more affordable and accessible for pregnant women. However, there are still some referrals that are based on the patient's own wishes or are not in accordance with BPJS Health Policy. This study was aimed to describe the incompatibility of ANC referrals for BPJS Health participants. This research is a descriptive study with a cross-sectional method. This study included all BPJS Health participant data referred from FKTP to the Obstetrics and Gynecology Clinic of Reda Bolo Hospital, Southwest Sumba, in the period March–June 2023. The appropriateness of ANC referrals in this study is based on Berita Acara Kesepakatan Bersama Panduan Penatalaksanaan Solusi Permasalahan Klaim INA-CBG BPJS Kesehatan 2019 No. JP.02.03/3/1693/2020. The majority of patients had a history of visiting 0-1 times in each trimester. In the first trimester, only a small proportion (1.1%) made more than one visit. In addition, the frequency of more than one visit was most common in the third trimester (15.6%). A total of 27 patients (15.1%) were categorized as ANC referrals that were not in accordance with BPJS Health Policy. There were still a number of patients who experienced referral discrepancies. Further research can be conducted to explore the factors that influence referral discrepancies and their impact on maternal and infant health.